SYEKH YUSUF AL-MAKASSARI: Studi Sejarah Dakwah dan Intelektual di Indonesia - Samsinas Samsinas (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
The development and Islamic preaching and intellectualism in Indonesia occured in two periods, traditional and modern. In the traditional period, there was one of the leading Muslim intellectuals, Syeikh Yusuf al-Makassari. His ideas and thought seem to give considerable effect to the development of religiousity in Muslim communities in Indonesia, perticularly in the areas where he lived and spread his preaching. His core ideas include; first, the manners of remembrance to Allah, which were so perfectly written that the salik and easily remember Allah. Second, monotheism in which, Syeikh Yusuf said that God's manifestation is mandatory, and nature is only possible. Therefore, equating of the two is misleading (kufr). His concept f wahdah al-wujud is very simple and easy to understand both in a sufistic and shari'ah way, especially among ahl sunnah.